2019
DOI: 10.1016/j.envsci.2019.06.015
|View full text |Cite|
|
Sign up to set email alerts
|

Households’ adaptation in a warming climate. Air conditioning and thermal insulation choices

Abstract: Adjustments in the final use of energy is a critical margin of adaptation for maintaining indoor thermal comfort. This paper explores how households have been adopting air conditioning and thermal insulation to cope with different climatic conditions, and how climatic factors interact with socio-economic, demographic, and household characteristics across eight OECD countries. Changes in the cumulative number of hot and cold days over the year, urbanization, demographics and household characteristics, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Examples of previous studies that have incorporated GLDAS data include (a) De Cian and Sue Wing (), De Cian et al . () for impact assessment studies in energy sector; and (b) Gao et al (), Zhong et al () for the analysis of regional environmental conditions and changes. A recent dataset (Mistry, ) has also incorporated temperature and precipitation data from GLDAS to assemble a comprehensive set of 71 climate extreme indices.…”
Section: Data Production Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of previous studies that have incorporated GLDAS data include (a) De Cian and Sue Wing (), De Cian et al . () for impact assessment studies in energy sector; and (b) Gao et al (), Zhong et al () for the analysis of regional environmental conditions and changes. A recent dataset (Mistry, ) has also incorporated temperature and precipitation data from GLDAS to assemble a comprehensive set of 71 climate extreme indices.…”
Section: Data Production Methodsmentioning
confidence: 99%
“…For instance, certain known limitations of GLDAS data, such as larger uncertainty in the surface air temperature estimates over high mountainous areas are well documented in literature (Ji et al , ). Users of the GLDAS‐derived data products, such as (De Cian et al , ; Mistry, ) and DegDays_ 0p25_1970_2018 in this study, are recommended to pay attention to the data caveats.…”
Section: Dataset Use Limitations and Scope For Further Workmentioning
confidence: 99%
“…The ever-increasing use of land, together with the ongoing climate changes, could lead to an increase in energy consumption for cooling in buildings, especially in temperate countries in Central and Southern Europe. The new European and national policies combine regulatory measures, energy labeling, and market incentives to achieve good solutions for each territory and to avoid trade-offs between adaptation behavior and mitigation objectives [25].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the technical data reported in Table 4 and the experience of the occupants, it is possible to affirm that (with good bioclimatic design) thermal comfort can be achieved without the use of air conditioning systems. This aspect allows the increase in energy-use trends for space cooling to be reversed [25].…”
Section: Technical and Economic Feasibilitymentioning
confidence: 99%
“…The strong association between income and household energy may also play a relevant role in a household's adaptation to climate change and the choice between air conditioning and thermal insulation choices. De Cian et al [58] found that the future adoption of thermal insulation might be more difficult given that the adoption of air conditioning is promoted by income, urbanisation and demographic trends.…”
Section: Analysis Of Direct and Indirect Links Between Indoor Temperamentioning
confidence: 99%